2014
DOI: 10.1007/s15010-013-0583-z
|View full text |Cite
|
Sign up to set email alerts
|

tst1-positive ST22-MRSA-IVa in healthy Italian preschool children

Abstract: A survey was performed in May 2013 to assess methicillin-resistant Staphylococcus aureus (MRSA) nasal colonization in healthy children attending 26 municipal daycare centres in Palermo, Italy. Of the 500 children, ten (2 %) tested positive. Eight MRSA isolates were tst1-positive ST22-MRSA-IVa, spa t223; the other two isolates were identified as ST1-IVa and ST398-V, respectively. tst1-positive ST22-MRSA, spa t223 has been previously identified only in the Middle Eastern area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…2 This CC22-MRSA-IV ''Middle Eastern Variant'' has been also described in Jordan and Saudi Arabia, 17,26 and more recently, in newborns and preschool children in Palermo, Italy. 10,11 The detection of this clone in Algeria confirms its wide dissemination in the Mediterranean and Middle East area. Moreover, within the two strains of ST5-MRSA, one could be identified as belonging to the so-called pediatric clone, which is widespread across America, Europe, Asia, and Australia, but is apparently infrequent in Africa.…”
Section: Discussionsupporting
confidence: 57%
“…2 This CC22-MRSA-IV ''Middle Eastern Variant'' has been also described in Jordan and Saudi Arabia, 17,26 and more recently, in newborns and preschool children in Palermo, Italy. 10,11 The detection of this clone in Algeria confirms its wide dissemination in the Mediterranean and Middle East area. Moreover, within the two strains of ST5-MRSA, one could be identified as belonging to the so-called pediatric clone, which is widespread across America, Europe, Asia, and Australia, but is apparently infrequent in Africa.…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, the susceptibility pattern of our clone (Table 2) does not match that of HA-EMRSA-15, whose isolates are uniformly resistant to ciprofloxacin and susceptible to co-trimoxazole and minocycline [26]. ST22-MRSA-IV strains could be a variant of UK-EMRSA-15 originating from ST22-MSSA spa t223 by means of local evolution, as suggested by Biber et al [23], knowing that the ST22-MRSA-IV strains observed in the present study showed traits similar to the predominant MRSA clone in the Gaza Strip [23] and to the one described in healthy Italian preschool children [22]. This clone mainly lacks exotoxin PVL, exhibits spa t223, and less often carries exotoxin gene tst.…”
Section: Discussionsupporting
confidence: 71%
“…It has been recently reported in healthy individuals (without associated healthcare risk factors) in Italy and the Middle East [22][23][24]. The origin of ST22-MRSA-IV strains circulating in the Tangier community could be HA-EMRSA-15 types, which are disseminated from hospitals to community environments, as several studies have indicated [6,25].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we also identified a spa t223 isolate, a type that has only been reported in the Middle East and in daycare centers in southern Italy. 36 Although the implications of this finding are unknown, it highlights the relative dearth of knowledge regarding the molecular epidemiology of S aureus outside health care environments.…”
Section: Discussionmentioning
confidence: 98%